La no valoración de la afectación de la capacidad de culpabilidad en delitos de violación sexual de menores, vulnera el derecho de obtener una sentencia justa en el distrito judicial de Piura. 2015 - 2016 - Leon Villa, Victoria del Carmen (2019)
ABSTRACT The objective in which the investigation was based was to determine, in what way, the non-assessment of the impact of the culpability of the person sentenced for rape of children under 10 years of age, in the presence of a serious psychic anomaly, pedophilia makes unimputable, violated the right of the sentenced to obtain a fair sentence, for lack of argumentation and lack of motivation, the same that should be issued respecting due process and effective procedural protection. To this end, the judgments issued by the collegiate, single-person and criminal courts of the judicial district of Piura for the period 2015-2016 have been analyzed, the result of which was that the judges did not assess the effect of the culpability in the sentences issued, Despite the fact that in these crimes there is the possibility that the perpetrators of these crimes are unimputable, because they suffer from the mental disorder of pedophilia, and they have been sentenced to custodial sentences when the right was the imposition of a security measure. The research was qualitative, using various methods such as analytical, synthetic, inductive and systematic, which served as the basis for processing the information obtained for our study; In addition, a structuring of the data was made reflected in a record table. Based on the aforementioned study, a significant lack of knowledge on the part of magistrates specializing in criminal matters regarding the impairment of culpability, unimpeatability, resulting in judgments unduly motivated and therefore contrary to parameters of a fair sentence in a Constitutional State of Law, purpose of every constitutional State.